(untitled) (Ha Noi, 1985)
Stories and reportages about Dien Bien Phu by Vo Nguyen Giap, Nguyen Huy Tuong, Nguyen Quang Sang, Vu Tu Nam
Keywords: Short stories,Truyện ngắn,Dien Bien Phu, Battle of,Trận đánh Điện Biên Phủ,Indochinese War,Chiến tranh Đông Dương; 1954,1954,1946-1954,1946 - 1954; Vietnam,Việt Nam